2019
DOI: 10.1039/c9cc05153h
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of hydrogen sulfide significantly reduces ROS stress and increases dopamine levels in transgenic C. elegans

Abstract: A novel peptide based system has been developed that exhibits slow and sustained H2S release thereby reducing hydrogen peroxide-induced oxidative stress and increasing dopamine levels in a transgenic C. elegans model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…A H 2 S-sensing naphthalimide-based peptide conjugate (HSNPc) was synthesized by both, solution phase [36][37][38] and solid-phase peptide synthesis using standard protocols. 39 4-Bromo naphthalic anhydride was used as a precursor molecule. Conjugation of alanine to this anhydride followed by substitution of bromine by dinitrobenzene probe at the fourth position of 4-bromo naphthalic anhydride carried out in solution phase.…”
Section: Resultsmentioning
confidence: 99%
“…A H 2 S-sensing naphthalimide-based peptide conjugate (HSNPc) was synthesized by both, solution phase [36][37][38] and solid-phase peptide synthesis using standard protocols. 39 4-Bromo naphthalic anhydride was used as a precursor molecule. Conjugation of alanine to this anhydride followed by substitution of bromine by dinitrobenzene probe at the fourth position of 4-bromo naphthalic anhydride carried out in solution phase.…”
Section: Resultsmentioning
confidence: 99%
“…No. D399) as described previously [21]. Brie y, stock solution (10 mM) was prepared fresh in absolute alcohol, which was diluted (100 µM) in phosphate buffer saline (for 1 X PBS Na 2 HPO 4 1.44 g, KH 2 PO 4 240 mg, NaCl 8 g, and KCl 200 mg).…”
Section: Quanti Cation Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…[36,37] Recent studies have shown that H 2 S plays a role in cell metabolism and redox balance. [38][39][40] ROS are ubiquitous in human organs and tis sues and are mainly produced by external stimulation or as byproducts of metabolic processes. [41,42] However, excessive ROS in cells causes oxidative stress, which may lead to oxida tive stressinduced diseases, including acute hypoxiaischemia/ reperfusion, degenerative diseases, epilepsy, and cardiovascular diseases.…”
Section: H 2 S-mediated Alleviation Of Ros In Mammalian Cell Communitiesmentioning
confidence: 99%